MIMO radar and communication spectrum sharing with clutter mitigation - Bo Li; Petropulu, Athina (Proceedings of the IEEE National Radar Conference (1996), 2016)
We address the co-existence of MIMO radars and a MIMO communication system. Unlike previous works, we consider a scenario in which the radar system operates in the presence of clutter. Both the radar and the communication system use transmit precoding. Initially, spectrum sharing is formulated as a problem that maximizes the radar SINR subject to the communication system meeting certain rate and power constraints. Due to the dependence of the clutter on the radar precoding matrix, the optimization with respect to the radar precoder is a maximization of a nonconvex function over a nonconvex feasible set. Since solving such problem is computationally intractable, we propose to maximize a lower bound of the SINR. In the resulting alternating maximization problem, the alternating iteration of the communication TX covariance matrix reduces to one SDP problem, while the iteration of the radar precoder is solved by a sequence of SOCP problems, which are more efficient and tractable than SDP. Simulation results validate the effectiveness of the proposed spectrum sharing method for scenarios with clutter.